1998
DOI: 10.1094/mpmi.1998.11.6.458
|View full text |Cite
|
Sign up to set email alerts
|

The Plasma Membrane H+-ATPase from the Biotrophic Rust Fungus Uromyces fabae: Molecular Characterization of the Gene (PMA1) and Functional Expression of the Enzyme in Yeast

Abstract: To study the molecular basis of biotrophic nutrient uptake by plant parasitic rust fungi, the gene (Uf-PMA1) encoding the plasma membrane H + -ATPase from Uromyces fabae was isolated. Uf-PMA1 exists probably as a single gene. However, two nearly identical sequences were identified; the similarity apparently is due to two Uf-PMA1 alleles in the dikaryotic hyphae. Multiple Uf-PMA1 transcripts were observed during early rust development, and reduced amounts of a single Uf-PMA1 mRNA were observed in haustoria and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 40 publications
3
53
0
Order By: Relevance
“…It is interesting that the catalytic domain from the AM isoforms GmPMA1 and GmHA5 appear more closely related to those from plant H ϩ -ATPases than to the catalytic domain of the fungal isoforms. Similar results were observed for U. fabae (Struck et al, 1998). Both the AM fungi and the rust fungus form biotrophic associations with their host plant, and it is tempting to speculate about either horizontal gene transfer or coevolution of the H ϩ -ATPase genes between these fungi and plants.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…It is interesting that the catalytic domain from the AM isoforms GmPMA1 and GmHA5 appear more closely related to those from plant H ϩ -ATPases than to the catalytic domain of the fungal isoforms. Similar results were observed for U. fabae (Struck et al, 1998). Both the AM fungi and the rust fungus form biotrophic associations with their host plant, and it is tempting to speculate about either horizontal gene transfer or coevolution of the H ϩ -ATPase genes between these fungi and plants.…”
Section: Discussionsupporting
confidence: 73%
“…For example, Brewer's yeast and fission yeast contain two ATPase genes (de Kerchove d 'Exaerde et al, 1996). In contrast, the biotrophic rust fungus U. fabae possesses only one gene, although different alleles are sometimes observed in the dikaryotic phase (Struck et al, 1998). In AM fungi, Ferrol et al (2000) isolated five different fragments corresponding to five putative isoforms of H ϩ -ATPase using a PCR approach with degenerate primers on genomic DNA from G. mosseae.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the enzyme was found to be signiWcantly more active in membranes isolated from haustoria compared to membranes from germlings (Struck et al, 1996). However, in agreement to the microarray data, Northern blot hybridisation experiments revealed that the PMA1-encoding gene was more strongly expressed in germ tubes and in vitro grown rust hyphae than in haustoria and rust-infected leaves (Struck et al, 1998).…”
Section: Discussionsupporting
confidence: 71%
“…While the function of most of these genes is unknown, PMA1 has been previously shown to encode a plasma membrane H + ATPase (Struck et al, 1998). Interestingly, the enzyme was found to be signiWcantly more active in membranes isolated from haustoria compared to membranes from germlings (Struck et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…These studies show that the bulk of sugars and amino acids are taken up by haustoria, although they represent only a minor volume and surface fraction of the total biotrophic mycelium. According to our model, an H + -ATPase generates the proton gradient across the haustorial plasma membrane, which provides the energy for the uptake of nutrients from the extrahaustorial matrix [36,37]. How these nutrients are translocated from the infected host cell across the extrahaustorial membrane is unknown.…”
Section: Biotrophic Developmentmentioning
confidence: 99%